New studies in textual interplay - Evans, Craig A.; Oropeza, B. J., 1961-; Sloan, Paul (Religious educator) (London [England] : T&T Clark, 2020)
"This volume features a body of work selected by Craig A. Evans, B. J. Oropeza, and Paul T. Sloan, designed to examine just what is meant by 'intertextuality,' including metalepsis and the controversial and exciting approach known as 'mimesis.' Beginning with an introduction from Oropeza which orients readers in a complex and evolving field, the contributors first establish the growing research surrounding the discipline, before examining important texts and themes in the New Testament Gospels and epistles"--
Preface -- Chapter 1. New Studies in Textual Interplay: An Introduction -- B.J. Oropeza, Azusa Pacific University, USA -- Chapter 2. Ancient Midrash in the Age of Intertextuality -- B.J. Oropeza, Azusa Pacific University, USA -- Chapter 3. Re-contextualization and the Multidimensional Approach to Scripture: Interpreting the Text of Matt 22:31-46 -- Erik Waaler, NLA University College, Norway -- Chapter 4. Mimesis and Criticism -- Karl Olav Sandnes, MF Norwegian School of Theology, Norway -- Chapter 5. Response to Karl Olav Sandnes -- Dennis R. MacDonald, Claremont School of Theology, USA -- Chapter 6. Israel's Last Prophet: Matthew 23:29-36 and the Intertextual Basis of Matthew's Rejected Prophet Christology -- David L. Turner, Cornerstone University, USA -- Chapter 7. The Good News of Isaiah and Rome in Mark 1:1 -- Adam Winn, Baylor University, USA -- Chapter 8. For Everyone Shall Be Salted with Fire -- Paul T. Sloan, Houston Baptist University, USA -- Chapter 9. Luke's Christology in Light of Old Testament Lament Echoes -- Channing L. Crisler, Anderson University, USA -- Chapter 10. The Marriage and Wedding Imagery of Jesus and Adam: The Intertextual Connection of John 19:23-37 and Genesis 2:18-25 -- Sunny Chen, Pilgrim Theological College, Australia -- Chapter 11. Multivalent Biblical Images in the Fourth Gospel and the Patristic Verbum Abbreviatum -- William M. Wright IV, Duquesne University, USA -- Chapter 12. The Covenant Curses, the Restoration, and the Inheritance of the Son: Jesus as Servant and Messiah in Gal 1:4 and Beyond -- Esau D. McCaulley, Northeastern Seminary, USA -- Chapter 13. Lawlessness, Idolatry, and Apostasy in the Book of Deuteronomy and in 1 John: An Old Message in a New Setting -- Max Rogland, Erskine Theological Seminary, USA -- Chapter 14. Final Reflection -- Steve Moyise, St Hild College, UK -- Bibliography
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Bible. -- Criticism, Textual; Intertextuality in the Bible; Biblical studies & exegesis; Electronic books